Convective Characteristics and Formation Conditions in an Extreme Rainstorm on the Eastern Edge of the Tibetan Plateau - Yongren Chen; Yueqing Li (Atmosphere, 2021)
From 7 July to 11 July 2013, an extreme rainstorm occurred in the Sichuan Basin (SCB) of China, which is located at the eastern edge of the Tibetan Plateau, causing severe floods and huge economic losses. The rainstorm event was associated with mesoscale convection systems (MCSs). In this paper, we analyze the evolution characteristics and formation conditions of the MCSs, and the results show that: (1) the continuous activity of MCSs was a direct cause of the formation of extreme rainstorms. Under an “east high and west low” circulation mode, the MCSs formed a “cloud cluster wave train” phenomenon from the plateau to the basin; that is, the MCSs over the basin developed strongly in the process of the MCSs over the plateau area weakening. (2) The activities of MCSs over the rainstorm area was related to ascending branches of the two vertical circulations and topographic gravity wave. Under the influence of meridional vertical circulation, MCSs could move in the south–north direction in the western SCB, while under the influence of zonal circulation, it was difficult for MCSs to develop in the descending airflow east of 106°E. (3) In the mountainous area of the western part of the SCB, the gravity wave stress was obvious and its direction was opposite to the direction of the lower southeast warm–moist airflow. This configuration was able to form a drag effect in the low-level airflow, which was conducive to the convergence of the wind field and strengthening of the vertical ascending movement. These findings help in further understanding the effects of vertical circulation and terrain on MCSs and extreme rainstorms.